INFORMATIZATION AS THE MOST IMPORTANT FACTOR IN THE SUCCESSFUL DEVELOPMENT OF HEALTHCARE FACILITIES - O. V. Strelchenko; M. I. Voevoda; A. L. Zaigraev; V. M. Chernyshev (Сибирский научный медицинский журнал, 2019)
Purpose of research – to assess the feasibility and effectiveness of informatization of practical health care medical organization. Material and methods: timing, statistical analysis, systematization, sociological (questionnaire) survey, the object of the study is a medical information system. Results and discussion. The main characteristics and principles of the medical information system, as well as the technology of its implementation in the institution of practical health care are described. The results of the use of the system for 5 years, important changes in the organization of the diagnostic and treatment process and management of the medical organization are presented. The introduction of the electronic medical card helped to reduce the time for its filling and delivery from the registry to the specialist’s office. The rational schemes of routing of citizens at carrying out of preventive examinations within the framework of the examination have been developed. At the same time, the main set of measures envisaged by it is currently carried out during 2–3 hours within one day (previously, citizens spent up to 4 hours for examination, sometimes two days). The medical disability electronic certificate used in the center, reduced the time of its registration, has ruled out re-visits of patients to clinics because of the wrong filling out, allowed us to realize the remote control over filling correctness. The module «Pharmacy» and the creation of a single nursing post contributed to a more rational accounting and use of medicines in the hospital Center, to reduce the cost of this article by 15 %. The use of the system in the transition to an effective contract allows quickly and objectively assessing the activities of employees and taking into account the cost of one point to calculate the amount of incentive payments, which employees can see in person. Conclusion. The results show that the informatization of medical organizations is the most important factor in the successful development of the institution, improves the quality and availability of medical care to the population.